Censorship and Adult Film Stars in Contemporary Indonesian Horror Cinema - Makbul Mubarak (ULTIMART Jurnal Komunikasi Visual, 2016)
There were uproars when film producer Ody Mulya Hidayat initiated to cast adult film stars in his film. It was Sora Aoi, a Japanese porn screen star. These uproars indicated multiple things. Some people are afraid that Aoi will nakedly act in front of Indonesian audiences. However, some others couldn’t wait the release date t0 be announced and buy tickets. All sights are suddenly upon the Indonesian Film Censorship Board, who is responsible to institutionally neutralize all the uproars. The formerly questionable institution is now at a big stake. Keywords : film, porn star, censorship